Preparation method of ceramic core for titanium alloy graphite mold casting
By using wooden molds and specific processes to prepare ceramic cores in titanium alloy casting, the problems of poor precision, low strength and difficult to remove ceramic cores are solved, and high-quality ceramic core preparation is achieved, satisfying the large and complex Casting requirements.
Patent Information
- Application Number
- CN202411300042.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-24
AI Technical Summary
The prior art has the problems of poor accuracy, low strength, difficulty in removing and poor surface quality of ceramic cores in titanium alloy casting, which is particularly difficult to meet the quality requirements of large and complex castings.
Designed with wooden molds, the contact surface layer and reinforcement layer are prepared by spraying paint, spraying mold release agent, grouting, and sanding. Combining low-temperature wax and refractory powder, the ceramic core is prepared by step roasting process to ensure the accuracy of the ceramic core and strength.
It improves the accuracy and strength of the ceramic core, simplifies the mold release process, reduces costs, ensures the surface quality of the castings, and meets the needs of precision casting of titanium alloys.
Smart Images

Figure CN119175343A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium and titanium alloy casting, and in particular to a method for preparing a ceramic core for titanium alloy graphite mold casting. Background Art
[0002] With the rapid development of aerospace, weapons and equipment and other fields, the design of titanium castings is increasingly tending towards large, complex, thin-walled and other characteristics. At present, single-piece, small-batch and large-size complex castings are mainly produced by machining graphite mold technology. However, due to the high thermal conductivity and poor high-temperature yield of graphite materials, graphite mold casting is prone to casting defects such as difficulty in filling, surface cracks, cold shut, flow marks, etc., especially for casting products with complex structures, large-size inner cavity structures, and difficult to repair welding or machining. At this time, it is difficult to meet the quality requirements by using only graphite molds, and the inner cavity structure must be formed with the help of ceramic cores. However, the current domestic production of ceramic cores is mainly used in high-temperature alloy and aluminum alloy investment casting, and its application in titanium and titanium alloy castings is still relatively narrow. The main problems are concentrated on core making materials and core making processes.
[0003] In terms of materials, in the existing public technology: silicon oxide and aluminum oxide ceramic cores are the most widely used, but they are mainly used for high-temperature alloys or aluminum alloys, not suitable for titanium alloys, and will cause serious chemical sand adhesion and reactive pore defects; yttrium oxide or zirconium oxide ceramic cores not only have high material costs, but also have high overall inertness and high strength, and are extremely difficult to remove, and are not suitable for large titanium alloy graphite mold casting; in addition, calcium oxide is also used to prepare ceramic cores, but due to the moisture absorption and hydration of calcium oxide, the surface of the core becomes crispy and slags off, resulting in scrapping or causing internal quality problems of the casting. Therefore, the ceramic cores of the above materials are difficult to be applied in the field of titanium alloy casting. The Chinese invention patent application with publication number CN103693976A discloses a method for preparing a ceramic core for casting titanium and titanium alloys. The main component of the core is silicon oxide. The method uses surface coating technology to prepare yttrium oxide or zirconium oxide coating on the surface of the silicon oxide core blank, and forms a composite silicon oxide ceramic core through enhanced sintering, which not only overcomes the high cost and difficulty of core removal of yttrium oxide or zirconium oxide ceramic cores, but also solves the problem of conventional silicon oxide cores being scrapped due to serious interface reaction with high-temperature titanium liquid. However, in the above method, silicon oxide is the main material, and yttrium oxide or zirconium oxide is the coating material. The entire blank undergoes at least one densification sintering process from preparation to casting. When the shrinkage of the surface layer does not match the shrinkage and deformation of the silicon oxide bottom layer, it will cause problems such as surface shedding and cracking. Once the coating of the silicon oxide core falls off, the protection will fail and it cannot be used.
[0004] In terms of preparation process, in the existing public technology regarding low-cost preparation technology, the ceramic core is coated in a prefabricated investment mold, but from the metal mold to the investment mold, the investment mold to the ceramic core blank, and then the finished ceramic core is obtained through densification and firing. The above three shrinkage processes make it difficult to control the size of the ceramic core, and often cause deformation, size out-of-tolerance and other problems that make it impossible to use. The Chinese invention patent application with publication number CN118237538A discloses a sand mold-ceramic composite mold for casting titanium or titanium alloy, a casting method and application, which requires the preparation of a metal mold, a metal mold molding wax mold, the preparation of a raw ceramic core, and sintering to obtain a cooked ceramic core. Not only is the shrinkage process difficult to control, but the wax mold also has the problems of shrinkage deformation and self-weight deformation, and difficulty in removal. At the same time, since the preparation of the wax mold requires the use of a wax press, the specifications of the wax mold are limited, and it cannot be used for large and complex castings. Summary of the invention
[0005] In view of this, the present invention aims to provide a method for preparing a ceramic core for titanium alloy graphite casting, so as to solve the problems of poor precision, low strength, difficulty in removal and poor surface quality of the prepared ceramic core.
[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] A method for preparing a ceramic core for titanium alloy graphite casting comprises the following steps:
[0008] Step 1: Design of wooden mold;
[0009] Step 2: Processing of wooden mold;
[0010] Step 3: Spray paint on the wooden mold;
[0011] Step 4: Spray release agent on the wooden mold;
[0012] Step 5: Wooden mold assembly and wax sealing;
[0013] Step 6: Grouting and sanding the working surface of the wooden mold to prepare the contact surface layer and reinforcement layer;
[0014] Step 7: demoulding;
[0015] Step eight: roasting.
[0016] Furthermore, in the step 4, 1 to 2 layers of release agent are sprayed on the surface of the wooden mold assembly block, and the thickness of a single layer spraying is 0.02 to 0.08 mm.
[0017] Furthermore, in step 4, the release agent is a low-temperature wax having a melting point of 60 to 80°C.
[0018] Furthermore, in the step three, polyurethane paint is sprayed on the surface of the wooden mold to make the surface roughness of the mold reach Ra1.6-3.2.
[0019] Furthermore, in the step six, a surface refractory powder with a particle size of 200-400 mesh and a first binder are mixed in a weight ratio of 4:1-6:1 to prepare a contact surface layer slurry, and the sanding material is a surface refractory powder with a particle size of 40-100 mesh. The contact surface layer slurry is poured into the pretreated wooden mold and sand is sprinkled. The operations of pouring the contact surface layer slurry and sprinkling sand are repeated at least twice to obtain a contact surface layer.
[0020] Furthermore, in the step six, a reinforcement layer refractory powder with a particle size of 100 to 300 mesh and a second binder are mixed in a weight ratio of 5:1 to 7:1 to prepare a reinforcement layer slurry, and the sanding material is a reinforcement layer refractory powder with a particle size of 30 to 60 mesh. The coating and sanding are repeated 3 to 6 times in sequence, and finally a layer of reinforcement layer slurry is coated to seal the slurry, and the reinforcement layer is obtained after drying.
[0021] Furthermore, the surface layer refractory powder is selected from at least one of yttria sand, yttria powder, zirconium oxide sand, and zirconium oxide powder; the first binder is selected from at least one of yttrium sol and zirconium acetate; the reinforcement layer refractory powder is selected from at least one of mullite sand and mullite powder; and the second binder is selected from silica sol.
[0022] Furthermore, in the step seven, a dewaxing kettle is used for rapid dewaxing, the dewaxing steam pressure is 6.5 to 7.5 kg, and the dewaxing time is 7 to 15 minutes.
[0023] Furthermore, in step eight, a roasting furnace is used with a step roasting process, the temperature is raised to 850-950°C at 5-8°C / min and kept for 120-240min, and then the temperature is raised to 1050°C at 10-15°C / min and kept for 240-360min to achieve densification sintering of the ceramic green body to obtain a ceramic core.
[0024] Compared with the prior art, the method for preparing a ceramic core for titanium alloy graphite casting according to the present invention has the following advantages:
[0025] (1) A wooden mold is used as a mold. The wooden mold has the advantages of low preparation cost, reusability, and certain strength. Using multiple wooden molds at the same time can improve production efficiency. Since the wooden mold does not deform due to gravity, it avoids shrinkage deformation and ensures the accuracy of the ceramic core.
[0026] (2) The preparation process of the wooden mold itself is not subject to other restrictions, and large-sized wooden molds can be prepared, which are suitable for casting large and complex titanium alloy castings.
[0027] (3) The thickness of the release agent sprayed inside the wooden mold is small, which is not only well compatible with the contact surface slurry, but also convenient for subsequent dewaxing.
[0028] (4) The core cleaning efficiency of the prepared ceramic core is improved, and the casting after core removal can significantly improve the cold shut and flow marks, and the surface roughness reaches Ra6.3μm, which can meet the requirements of titanium alloy precision casting. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0030] Figure 1 This is the appearance of the ceramic body after demoulding in Example 1 of the present invention;
[0031] Figure 2 Schematic diagram of casting of ceramic core graphite mold assembly of Examples 1-2 and Comparative Examples 1-2;
[0032] Figure 3 This is a comparison chart of core stripping efficiency;
[0033] Figure 4 The surface roughness of the castings after the ceramic cores of Examples 1 to 2 and Comparative Examples 1 to 2 are removed from the core;
[0034] Figure 5 This is a metallographic structure diagram of the casting surface after the ceramic core is de-cored in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with specific embodiments. It should be noted that the data in the following experimental examples are obtained by the inventor through a large number of experiments. Due to space limitations, only a part of them is shown in the specification, and those of ordinary skill in the art can understand and implement the present invention under these data. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these changes or modifications also fall within the scope protected by the present application.
[0036] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0037] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.
[0038] A method for preparing a ceramic core for titanium alloy graphite casting of the present invention comprises the following steps:
[0039] Step 1: Design of wooden mold;
[0040] Specifically, a ceramic core mold for a casting inner cavity is designed according to the shape and size of a large-sized graphite titanium alloy casting, and the mold adopts a split combined wooden mold.
[0041] Step 2: Processing of wooden mold;
[0042] Specifically, a plurality of wooden mold assembly blocks are manufactured by processing wooden mold blanks through a numerically controlled machine tool, and the size error does not exceed 0.1 mm.
[0043] Step 3: Spray paint on the wooden mold;
[0044] Specifically, polyurethane paint is sprayed on the surface of the wooden mold to make the mold surface roughness reach Ra1.6 to 3.2. The polyurethane paint has heat resistance and is convenient for the subsequent baking process.
[0045] Step 4: Spray release agent on the wooden mold;
[0046] Specifically, 1 to 2 layers of release agent are sprayed on the surface of the wooden mold assembly block, and the thickness of a single layer spraying is 0.02 to 0.08 mm, which is convenient for subsequent demoulding. The release agent is a low-temperature wax with a melting point of 60 to 80° C. More specifically, in order to ensure the uniformity of spraying, a 3D spraying process is used for spraying.
[0047] Step 5: Wooden mold assembly and wax sealing;
[0048] Specifically, after the split wooden formwork is assembled, the joint seams are repaired with wax to make the joint seams smooth.
[0049] Step 6: Grouting and sanding the working surface of the wooden mold to prepare the contact surface layer and reinforcement layer;
[0050] Specifically, a surface refractory powder with a particle size of 200-400 mesh and a first binder are mixed in a weight ratio of 4:1-6:1 to prepare a contact surface layer slurry. The sanding material is a surface refractory powder with a particle size of 40-100 mesh. The contact surface layer slurry is poured into the pretreated wooden mold and sand is sprinkled. The pouring of the contact surface layer slurry and the sanding operations are repeated at least twice to obtain the contact surface layer.
[0051] The reinforcement layer slurry is prepared by mixing the reinforcement layer refractory powder with a particle size of 100-300 mesh and the second binder in a weight ratio of 5:1-7:1. The sanding material is the reinforcement layer refractory powder with a particle size of 30-60 mesh. Repeat the application and sanding for 3-6 layers, and finally apply a layer of reinforcement layer slurry for sealing. After drying, the reinforcement layer is obtained. The drying time for each layer is not less than 6 hours.
[0052] More specifically, the surface layer refractory powder is selected from at least one of highly inert yttria sand, yttria powder, zirconium oxide sand, and zirconium oxide powder; the first binder is selected from at least one of yttrium sol and zirconium acetate; the reinforcement layer refractory powder is selected from at least one of mullite sand and mullite powder with high refractoriness; the second binder is selected from silica sol.
[0053] The present invention uses a contact surface layer and a reinforcement layer on the working surface of a wooden mold to prepare a ceramic core blank, and the ceramic core blank adopts a layer-by-layer preparation technology, different types of refractory materials are staggered and compensated, and multi-granularity composite grading improves interlayer bonding strength, thereby reducing material costs.
[0054] In addition, since low-temperature wax is sprayed on the surface of the wooden mold as a release agent, the contact surface slurry and the low-temperature wax have good wettability. The contact surface slurry enters the wooden mold through grouting and adheres to the surface of the release agent, avoiding the complexity of the operation of using the slurry coating method and helping to simplify the operation.
[0055] Step 7: demoulding;
[0056] Specifically, the dewaxing kettle is used for rapid dewaxing, the dewaxing steam pressure is 6.5-7.5 kg, the dewaxing time is adjusted to 7-15 minutes according to the size of the parts, and the exhaust needs to be discharged slowly. After the dewaxing is completed, the wooden mold is disassembled to obtain the ceramic green body. The wooden mold can be reused, which is conducive to cost saving.
[0057] Step eight, roasting;
[0058] Specifically, a step-by-step roasting process is used in a roasting furnace, with the temperature increased by 5-8°C / min to 850-950°C and kept for 120-240min, and then increased by 10-15°C / min to 1050°C and kept for 240-360min to achieve densification sintering of the ceramic green body and obtain a ceramic core.
[0059] The present invention discloses a method for preparing a ceramic core for titanium alloy graphite casting, which uses a wooden mold as a mold. The wooden mold has the advantages of low preparation cost, reusability, and certain strength. The use of multiple wooden molds at the same time can improve production efficiency. Since the wooden mold does not deform due to gravity, shrinkage deformation is avoided, and the accuracy of the ceramic core is ensured. The preparation process of the wooden mold itself is not subject to other restrictions, and a large-scale wooden mold can be prepared, which is suitable for casting large and complex titanium alloy castings. The release agent sprayed in the wooden mold has a small thickness, which is not only well compatible with the contact surface slurry, but also convenient for subsequent convenient dewaxing.
[0060] Example 1
[0061] According to the shape and size of the graphite titanium alloy casting, the ceramic core mold for the casting cavity is designed, and the mold adopts a split modular wooden mold. The wooden mold blank is processed by CNC machine tools to prepare multiple wooden mold assembly blocks, and the dimensional error does not exceed 0.1mm. After the wooden mold is prepared, polyurethane paint is sprayed on the surface of the wooden mold to make the surface roughness of the wooden mold reach Ra1.6~3.2. After the spraying is completed, the 3D printing spraying process is used to spray low-temperature wax on the surface of the wooden mold assembly block, and the melting point of the low-temperature wax is 60~80℃. The low-temperature wax is sprayed in 2 layers, the thickness of the first layer is 0.08mm, and the thickness of the second layer is 0.05mm. After the spraying is completed, the split wooden mold is assembled, and the joints are repaired with wax to make the joints smooth.
[0062] Yttrium oxide sand with a particle size of 200-400 mesh and yttrium sol are mixed in a weight ratio of 4:1 to prepare a contact surface layer slurry, and yttrium oxide sand with a particle size of 40-100 mesh is used as a contact surface layer sanding material. The contact surface layer slurry is poured into the pretreated wooden mold, and then sand is sprinkled. The operation of pouring the contact surface layer slurry and sanding is repeated twice to prepare the first layer and the second layer.
[0063] Mullite sand with a particle size of 100-300 mesh and silica sol are mixed in a weight ratio of 5:1 to prepare a reinforcement layer slurry, and mullite sand with a particle size of 30-60 mesh is used as the reinforcement layer sanding material. After the contact surface layer is dry, the reinforcement layer slurry is applied and sanded, and the application and sanding are repeated for 4 layers in sequence. Finally, a layer of reinforcement layer slurry is applied to seal the slurry, and the reinforcement layer is obtained after drying. The drying time of each of the above layers shall not be less than 6 hours.
[0064] Dewaxing is carried out in a dewaxing kettle, the dewaxing steam pressure is 6.5-7.5 kg, the dewaxing time is 7 minutes, and the exhaust needs to be discharged slowly. After dewaxing is completed, the wooden mold is disassembled to obtain the ceramic green body. Using a roasting furnace, a step roasting process is adopted, the temperature is raised to 850℃ at 5℃ / min and kept for 120 minutes, and then the temperature is raised to 1050℃ at 10℃ / min and kept for 240 minutes to achieve the densification sintering of the ceramic green body and obtain a ceramic core.
[0065] Example 2
[0066] The shape and size of the wooden mold obtained by processing in Example 2 are the same as those in Example 1. After the preparation of the wooden mold is completed, polyurethane paint is sprayed on the surface of the wooden mold to make the surface roughness of the wooden mold reach Ra1.6~3.2. After the painting is completed, the 3D printing spraying process is used to spray low-temperature wax on the surface of the wooden mold assembly block, and the melting point of the low-temperature wax is 60~80℃. Spray 2 layers of low-temperature wax, the thickness of the first layer is 0.06mm, and the thickness of the second layer is 0.02mm. After the spraying is completed, the split wooden mold is assembled, and the joints are repaired with wax to make the joints smooth.
[0067] Zirconia sand with a particle size of 200-400 mesh and zirconium acetate are mixed in a weight ratio of 6:1 to prepare a contact surface slurry, and zirconium oxide sand with a particle size of 40-100 mesh is used as a contact surface sanding material. The contact surface slurry is poured into the pretreated wooden mold, and then sand is sprinkled. The operation of pouring the contact surface slurry and sanding is repeated twice to prepare the first layer and the second layer.
[0068] Mullite powder with a particle size of 100-300 mesh and silica sol are mixed in a weight ratio of 7:1 to prepare a reinforcement layer slurry, and mullite sand with a particle size of 30-60 mesh is used as the reinforcement layer sanding material. After the contact surface layer is dry, the reinforcement layer slurry is applied and sanded, and the application and sanding are repeated for 6 layers in sequence. Finally, a layer of reinforcement layer slurry is applied to seal the slurry, and the reinforcement layer is obtained after drying. The drying time of each of the above layers shall not be less than 6 hours.
[0069] Dewaxing is carried out in a dewaxing kettle, the dewaxing steam pressure is 6.5-7.5 kg, the dewaxing time is 15 minutes, and the exhaust needs to be discharged slowly. After dewaxing is completed, the wooden mold is disassembled to obtain the ceramic green body. Using a roasting furnace, a step roasting process is adopted, the temperature is raised to 950℃ at 8℃ / min and kept for 240 minutes, and then the temperature is raised to 1050℃ at 15℃ / min and kept for 360 minutes to achieve the densification sintering of the ceramic green body and obtain a ceramic core.
[0070] Comparative Example 1
[0071] The preparation method of Comparative Example 1 is the same as that of Example 1, except that when the low-temperature wax is sprayed on the wooden mold, two layers are sprayed, and the thickness of each layer is 1 mm.
[0072] Comparative Example 2
[0073] Comparative Example 2 is a graphite core.
[0074] The ceramic cores of Examples 1 and 2 prepared by the preparation method of the present invention are completely formed, have smooth surfaces, no powdery feeling, and no cracks. Figure 1 The ceramic body after demoulding prepared in Example 1 is shown as having a complete and smooth appearance. The thickness of the low-temperature wax sprayed on the wooden mold in Comparative Example 1 is relatively thick, which will affect the appearance of the ceramic body after demoulding, and a small amount of tiny unevenness will appear, causing the surface to be rough. Therefore, the thickness of the sprayed low-temperature wax should be controlled during the preparation of the ceramic core. Figure 2 shown.
[0075] Examples 1-2 and Comparative Examples 1-2 use mechanical core removal, such as Figure 3The figure shows the core cleaning effect after casting. The composite cleaning time of Example 1 is 26 minutes, the composite cleaning time of Example 2 is 25 minutes, the composite cleaning time of Comparative Example 1 is 36 minutes, and the composite cleaning time of Comparative Example 2 is as high as 50 minutes. Compared with Comparative Examples 1 and 2, the core cleaning efficiency of Examples 1 and 2 using the preparation method of the present invention is significantly improved.
[0076] like Figure 4 The figure is the roughness appearance of the casting surface after the ceramic core is de-cored. The castings prepared by the ceramic cores of Example 1, Example 2 and Comparative Example 1 can significantly improve the cold shut and flow marks after de-coring, and the surface roughness reaches Ra6.3μm, which can meet the requirements of titanium alloy precision casting. However, after the graphite core of Comparative Example 2 is de-cored, the casting has flow marks and obvious cold shut. Figure 5 The metallographic structure of the casting surface obtained by using the ceramic core prepared in Example 1 is shown in the figure. The ceramic core forms a strip-shaped α phase near the surface, and no obvious contamination layer is observed. The metallographic structure of the casting surface obtained by using the ceramic core prepared in Example 2 also has no contamination layer. Due to space reasons, the metallographic structure of the casting surface obtained by using Example 2 is not shown in the present invention.
[0077] It can be seen that the method for preparing a ceramic core for titanium alloy graphite mold casting of the present invention can obtain a ceramic core with good surface quality, high thermal stability and easy removal, thereby avoiding problems such as deformation and dimensional deviation.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a ceramic core for titanium alloy graphite casting, characterized in that: The steps include: Step 1: Design of wooden mold; Step 2: Processing of wooden mold; Step 3: Spray paint on the wooden mold; Step 4: Spray release agent on the wooden mold; Step 5: Wooden mold assembly and wax sealing; Step 6: Grouting and sanding the working surface of the wooden mold to prepare the contact surface layer and reinforcement layer; Step 7: demoulding; Step 8: roasting.
2. The method for preparing a ceramic core for titanium alloy graphite casting according to claim 1, characterized in that: In the step 4, 1 to 2 layers of release agent are sprayed on the surface of the wooden mold assembly block, and the thickness of a single layer spraying is 0.02 to 0.08 mm.
3. The method for preparing a ceramic core for titanium alloy graphite casting according to claim 1, characterized in that: In the step 4, the release agent is low-temperature wax with a melting point of 60 to 80°C.
4. The method for preparing a ceramic core for titanium alloy graphite casting according to claim 1, characterized in that: In the step three, polyurethane paint is sprayed on the surface of the wooden mold to make the mold surface roughness reach Ra1.6-3.
2.
5. The method for preparing a ceramic core for titanium alloy graphite casting according to claim 1, characterized in that: In the step six, a surface refractory powder with a particle size of 200-400 mesh and a first binder are mixed in a weight ratio of 4:1-6:1 to prepare a contact surface layer slurry, and a surface refractory powder with a particle size of 40-100 mesh is selected as the sanding material. The contact surface layer slurry is poured into the pretreated wooden mold and sand is sprinkled. The pouring of the contact surface layer slurry and the sprinkling of sand are repeated at least twice to obtain a contact surface layer.
6. The method for preparing a ceramic core for titanium alloy graphite casting according to claim 5, characterized in that: In the step six, a reinforcement layer refractory powder with a particle size of 100 to 300 mesh and a second binder are mixed in a weight ratio of 5:1 to 7:1 to prepare a reinforcement layer slurry, and a reinforcement layer refractory powder with a particle size of 30 to 60 mesh is selected as the sanding material. The coating and sanding are repeated 3 to 6 times in sequence, and finally a layer of reinforcement layer slurry is coated to seal the slurry, and the reinforcement layer is obtained after drying.
7. The method for preparing a ceramic core for titanium alloy graphite casting according to claim 6, characterized in that: The surface layer refractory powder is selected from at least one of yttria sand, yttria powder, zirconium oxide sand, and zirconium oxide powder; the first binder is selected from at least one of yttrium sol and zirconium acetate; the reinforcement layer refractory powder is selected from at least one of mullite sand and mullite powder; the second binder is selected from silica sol.
8. The method for preparing a ceramic core for titanium alloy graphite casting according to claim 5, characterized in that: In the step seven, a dewaxing kettle is used for rapid dewaxing, the dewaxing steam pressure is 6.5 to 7.5 kg, and the dewaxing time is 7 to 15 minutes.
9. The method for preparing a ceramic core for titanium alloy graphite casting according to claim 5, characterized in that: In the step eight, a roasting furnace is used with a step roasting process, the temperature is raised to 850-950° C. at 5-8° C. / min and kept at that temperature for 120-240 min, and then the temperature is raised to 1050° C. at 10-15° C. / min and kept at that temperature for 240-360 min to achieve densification sintering of the ceramic green body and obtain a ceramic core.
Citation Information
Patent Citations
Method for preparing silicon oxide-based ceramic core for titanium and titanium alloy casting
CN103693976A
Sand mold-ceramic composite casting mold for titanium or titanium alloy casting, casting method and application
CN118237538A
Cited By
Preparation method of large-size ceramic core for titanium alloy casting
CN120268964A
A method for preparing a large-size ceramic core for titanium alloy casting
CN120268964B
Preparation method of graphite and ceramic core composite cavity for titanium alloy casting based on 3D printing technology
CN120502666A
Preparation method of ceramic core for titanium alloy casting
CN121289409A
